Smoking habits in French farmers: a cross-sectional study - Pauline Roux; Alicia Guillien; Thibaud Soumagne; Ophélie Ritter; Jean-Jacques Laplante; Cécile Travers; Jean-Charles Dalphin; Gérard Peiffer; Lucie Laurent; Bruno Degano (BMC, 2017)
Abstract Background Farmers are exposed to multiple air contaminants that may interact with tobacco smoking in the development of respiratory diseases. Farmers are currently considered to smoke less than non-farmers, but precise data in different categories of age and farming activities are lacking. Methods Smoking habits were studied in a cross-sectional study involving 4105 farmers and 996 non-farming controls aged 40-74 years in 9 French departments between October 2012 and May 2013. Three age groups were defined (40-54, 55-64 and 65-74years). Farmers were divided into four activity groups, namely cattle breeders, livestock farmers working in confined spaces, crop farmers and others. Smoking prevalence was compared between farmers and controls, and odds ratios (ORs) for smoking adjusted for age were calculated. Results The adjusted OR for ever-smoking was lower among farmers than among non-farmers in all age categories, but the ORs for current smoking were similar in farmers and controls. Smoking prevalence varied according to the type of farming activity, and was lower than in non-farming controls only among cattle breeders and confined livestock farmers. In farmers, the proportion of smokers was higher in the youngest age categories compared with the older age classes. Conclusions Our results confirm that the prevalence of ever-smokers is lower in farmers than in non-farmers. Nevertheless, our data show that active smoking prevalence is similar in farmers and in non-farmers. This suggests that farmers, just like non-farmers, should be targeted by primary prevention campaigns against smoking.